HUKUMAN BAGI PELAKU KEJAHATAN DENGAN MASALAH KEJIWAAN - Farra Dinda Mulyadi Putri; Cindy Carolin, Jusini Delas Halifah, Wiji Aulia Fatiha, Ikawati Ratnaduhita, Tugimin Supriyadi (INTELIGENSIA MEDIA, 2025)
This study examines the treatment of criminal offenders with mental disorders in the Indonesian criminal justice system. The focus is on identifying weaknesses in the existing legal framework, case prevalence, the role of forensic psychiatrists, rehabilitative approaches, and relevant case studies. Using a qualitative method based on a literature review, the findings reveal that Article 44 of the Indonesian Criminal Code, while serving as the main legal foundation, suffers from unclear criteria for mental disorders and a heavy reliance on psychiatric reports without standardized guidelines. The prevalence of offenders with mental disorders reaches 12% of all criminal cases, while the recidivism rate for offenders sentenced to prison stands at 65%, significantly higher than the 25% rate for those undergoing rehabilitation. The case study of Ryan Jombang highlights a lack of understanding of mental disorders in legal decision-making, whereas a rehabilitative approach for offenders with bipolar disorder demonstrates more humane and effective outcomes. This study recommends reforms such as standardized psychiatric evaluation guidelines, increased rehabilitation facilities, legal professionals' training, and campaigns to reduce stigma against mental disorders. These reforms are expected to create a more inclusive, just, and humane legal system